DSL-023 The Cost Analysis of Introducing the Two-Bin Replenishment System For Medical Devices, Antiseptics and Intravenous Fluids in a Geriatric Hospital. (12th March 2013) - Lelieur, F; Goffinet, P; Simonet, G; Chaumard, V; Derain, L
Abstract : Background: The two-bin replenishment system has been launched in some public hospitals of Lyon for medical devices, antiseptics and intravenous fluids. Purpose: To make a cost analysis of setting up the two-bin system in a hospital that has eleven wards. Materials and Methods: We identified the cost differences between the new two-bin replenishment system and the previous one from the perspective of the hospital. Self-assessment questionnaires aimed to gather the following information: the time spent using the original system and the new one over a period of one week, the time spent setting up the new system. The questionnaires were carried out on the wards, pharmacy and with the staff in charge of the setting up. Then we gave a value to the times collected using the amount charged for salaries in 2011. The amount of products returned to the pharmacy was used as an indicator of the cost savings between the two systems. We also collected the cost of furniture. We finally made an amortisation schedule of the collected costs. Results: Eight out of the eleven wards answered the self-assessment questionnaire. The value of staff time saved with the two bin replenishment system was found to be €13, 800 per year. The difference in cost between the new and the original stock was around €7600. We compared these savings with the cost of setting up the new system. It cost €24, 500 in manual labour expenses and €35, 600 for the furniture and renovation works. The amortisation schedule shows a return on investment in 3 years. Conclusions: This study reinforced our wish to develop this type of replenishment in our other public hospitals as its safety benefit has been published in a previous report (MEAH report – September 2006). No conflict of interest.